Constructing Teacher’s Moral Leadership in Imam Nawawi’s Educational Ethics: A Social Learning Perspective - Muhammad Tauhid Abdurrahman; Kharis Syuhud Mujahada (Al-Qalam Institue, 2026)
This study aims to reconstruct the concept of teacher exemplarity (keteladanan guru) in Adab al-‘Ālim wa al-Muta‘allim by Imam al-Nawawi through the lens of Bandura’s social learning theory and to examine its implications for Teacher Professional Development (TPD) within Islamic Educational Management. The study employed a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol. A total of 18 publications, including theoretical studies, conceptual papers, policy reports, and systematic reviews published between 1977 and 2025, were selected and analyzed using thematic analysis. The findings identified five key social learning mechanisms reflected in both the classical text and contemporary literature: modeling, attention, retention, reproduction, and motivation. These mechanisms demonstrate that teacher professional development extends beyond technical competence, functioning as a continuous process of moral and spiritual learning through exemplary behavior. Teachers serve as moral leaders whose actions and ethical consistency are observed, internalized, and reproduced within educational environments. The study implies that TPD programs and educational management practices should integrate moral exemplarity, value internalization, and continuous professional learning to strengthen teacher development and institutional effectiveness in Islamic education.